Phase field modelling of the hydro-mechanical coupling failure mechanisms of fissured rock masses - Kou, Miaomiao; Li, Chenxi; Wang, Yan; Liu, Fei (Frontiers in Earth Science, 2025)
Exploring the mechanical response and damage mechanism of fractured rocks under hydro-mechanical coupling is a key approach to address the safety and stability problems of rock engineering under hydro-mechanical coupling conditions. Based on Biot theory and pore elasticity theory, a numerical simulation method of hydro-mechanical coupled phase field is developed, and a staggered time integration scheme is proposed to obtain stable solutions of fluid pressure and solid deformation, in which the obtained control equations adopt the volume strain separation and partial strain separation of the elasticity theory of fully saturated porous media. Two different numerical examples of fluid permeability tests and hydraulic fracturing with natural fracture interaction are used for validation. During the comparison of the numerical model with the analytical solution, the numerical results and the previous data are in better agreement, which verifies the validity and correctness of the model method. In addition, in order to investigate the unloading damage mechanism in the actual engineering excavation process, a hydro-mechanical coupled unloading damage model was established by combining numerical examples of borehole injection tests to simulate the whole process of fracture rock propagation damage under the dual conditions of hydro-mechanical coupling and surrounding pressure unloading. The study shows that fluid infiltration and hydraulic fracture crack expansion are mainly controlled by tensioning action, while mixed tensile-shear crack expansion and connection dominate the final damage mode during coupled hydro-mechanical unloading damage.